OPEN EMPLOYEE RECRUITMENT STRATEGY TO IMPROVE THE QUALITY OF HUMAN RESOURCES AT PT SANGA GROUP INDONESIA - Turhamun Turhamun; Alfizi Alfizi; Faizal Rizky Yuttama (Riviera Publishing, 2025)
This study explores the implementation of an open employee recruitment strategy at PT. Sanga Group Indonesia to enhance the quality of human resources in the convection and screen-printing industry. The research adopts a qualitative descriptive approach involving interviews, observations, and document analysis during a six-month internship. Findings reveal that structured recruitment through SOPs, the adoption of digital platforms, and a strong focus on competency-based selection significantly improve workforce quality, reduce turnover, and enhance production efficiency. Despite the benefits, challenges such as limited digital literacy among applicants and incomplete automation in selection processes still hinder full optimization. The study also highlights the critical role of employer branding in attracting and retaining qualified candidates. These insights offer practical implications for SMEs in labor-intensive sectors aiming to modernize their HR strategies through technology and structured procedures.